The Sumerian Wonder. With the collaboration of M. Brady, M. von Haynal, G. Enderlin and Dr. E. Novotny - Badiny, Francisco Jos (1974)
Introduced by Dr. Ismael Quiles, S.J.; defense of Sumerian-Hungarian relationship; 213-218: The Sumerian Seals of Buenos Aires.